Differentiate. f(x) = (4x2 - 8) - (1 + 4x3) f'(x) = 32x(4x2 - 8) 3 - 12x2(1 + 4x3,4 f'(x) = 32x(4x2 - 8) 3 - 60x?(1 + 4x3,4 f'(x) = (32x-8)(4x2 - 8)3 - (1 + 60x?)(1 + 4x334 f'(x) = 4(4x2 - 8) 3 - 5(1 +4x3)4
![Differentiate fx 4x2 8 1 4x3 fx 32x4x2 8 3 12x21 4x34 fx 32x4x2 8 3 60x1 4x34 fx 32x84x2 83 1 60x1 4x334 fx 44x2 8 3 51 4x34 class=](https://us-static.z-dn.net/files/d1a/e8512e3055b61ac8b377cbaba822dc8a.png)
we have
f(x)=(4x2-8)^4-(1+4x^3)^5
so
f'(x)=4(4x^2-8)^3(8x)-5(1+4x^3)^4(12x^2)
f'(x)=32x(4x^2-8)-60x^2(1+4x^3)^4